Analysis of Bank Health Levels Using the Camel Method at BUMN Commercial Banks Listed - Ayusningtyas, Anthonia Fransisca; Yendra, Yendra; Marihi, La Ode (Advances in Management & Financial Reporting, 2024)
Purpose: This study uses the CAMEL method to evaluate the health level of state-owned banks listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, which includes aspects of capital adequacy, asset quality, management, earnings, and liquidity. Research Design and Methodology: This study uses secondary data from the annual financial statements of four state-owned banks selected through purposive sampling. The CAMEL method was applied to analyze these banks' financial soundness. Findings and Discussion: The results show that state-owned banks generally maintained a healthy financial condition during the study period. However, some financial ratios, such as NPM and ROA, fluctuated. This indicates the need to improve operational efficiency and cost management. Implications: This study guides bank management in improving operational efficiency and risk management to maintain financial stability. Regulators can also use these findings to evaluate and enhance banking policies.